Counting maximal matchings in linear polymers - Došlić, Tomislav (Ars mathematica contemporanea, 2016)
A matching ?$M$? in a graph ?$G$? is maximal if it cannot be extended to a larger matching in ?$G$?. In this paper we show how several chemical and technical problems can be successfully modeled in terms of maximal matchings. We introduce the maximal matching polynomial and study its basic properties. Then we enumerate maximal matchings in several classes of graphs made by a linear or cyclic concatenation of basic building blocs. We also count maximal matchings in joins and corona products of some classes of graphs.
Keywords: cactus chain; cactus graph; corona product; kaktusna veriga; kaktusni graf; kronski produkt; maksimalno prirejanje; maximal matching; maximal matching polynomial; Padovan numbers; Padovanova števila; Perrin numbers; Perrinova števila; polinom maksimalnega prirejanja